Bezbednosni sistem u Republici Makedoniji - izazovi i perspektive - Kozarev, Atanas (Kriminalističke teme, 2008)
According to Constitution, Republic of Macedonia is unitary state in which there are guarantee the basic human rights and freedoms for all citizens according to the liberal and democratic principals. Establishment of standards, in the field of human freedoms and rights, justice and internal affairs were basis for building of contractual relations with European Union and assigning the Agreement for stabilization and association between Republic of Macedonia and European community. On the way of Euro - Atlantic integrations through reforms in political, economic and other fields, one of the most important reforms were reforms in security sector and their adaptation to postulate on legitimate state, democratic principals, legality and legitimate in practicing the powder in our multiethnic community. In these efforts, important place took implementation of Framework agreement in which there are guaranteed and promoted peaceful and harmonic development of citizen community, respect of ethnical identity and interests of all citizens in Republic of Macedonia. On this way through the years of practice in security, promote Macedonia on regional and international level as a leader in respect of human rights and freedoms of different ethnical communities in the countries.